Adhesive composition for laminating electromagnetic steel sheets
The adhesive composition for laminated electromagnetic steel sheets, featuring a combination of three or more functional epoxy resin, high-Tg phenoxy resin, and amine-based latent curing agent, addresses the challenges of temperature-dependent toughness, tack-free handling, and long-term adhesive durability, resulting in enhanced performance and reliability of laminated iron cores.
Patent Information
- Application Number
- JP2023529667
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-21
- Filing Date
- 2022-04-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-04-28
AI Technical Summary
Conventional adhesive compositions for laminated electromagnetic steel sheets fail to achieve excellent toughness over a wide temperature range, maintain tack-free properties during storage and handling, and ensure durable adhesive performance after long-term storage.
The adhesive composition combines a three or more functional epoxy resin with a phenoxy resin having a glass transition temperature exceeding 120°C and an amine-based latent curing agent, optimizing the content of these components to achieve a glass transition temperature of the cured adhesive exceeding 160°C.
This composition provides excellent tack-free properties, maintains adhesive performance after long-term storage, and exhibits superior toughness over a wide temperature range, including high temperatures, ensuring the integrity of laminated iron cores.
Smart Images

Figure 0007660675000001 
Figure 0007660675000002 
Figure 0007660675000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition for laminating electrical steel sheets. [Background technology]
[0002] Conventionally, for example, laminated cores have been used in stators or rotors of electric motors, generators, transformers, etc. Laminated cores are generally formed by laminating a plurality of electromagnetic steel sheets bonded together with an adhesive composition.
[0003] Regarding laminated cores, for example, Patent Document 1 discloses that adhesive layers of laminated electromagnetic steel sheets are made of an organic resin (eg, epoxy resin) having a glass transition temperature or softening temperature of 50°C to 150°C.
[0004] Patent Document 2 relates to an annular laminated core material and a manufacturing method for the annular laminated core material, and discloses that a resin composition consisting of an epoxy group-containing phenoxy resin and a polyamide resin is used as an adhesive when manufacturing a laminated sheet of aramid paper to be used as an insulating sheet for the laminated core material.
[0005] Patent Document 3 relates to a manufacturing method for an adhesive laminated iron core in which multiple laminated iron core thin plates are bonded together with an adhesive, and discloses that as one indicator of the heat resistance of the adhesive, the tensile strength after being held at 300°C for 1 hour in a nitrogen atmosphere is preferably 30 MPa or more.
[0006] Patent Document 4 relates to a laminated iron core used in motor rotors, motor stators, transformers, etc., and a manufacturing method thereof, and discloses a non-oriented electrical steel sheet composition that includes a first composition containing a water-soluble epoxy resin and inorganic nanoparticles which are SiO2, TiO2, ZnO, or a combination thereof, and an inorganic additive which is phosphoric acid (H3PO4), sodium hydroxide (NaOH), or a combination thereof, wherein the inorganic nanoparticles are substituted with terminal substituents of the water-soluble epoxy resin, and the epoxy resin is a multifunctional epoxy resin having three or more epoxy groups. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2002-146492 A [Patent Document 2] JP 2020-171171 A [Patent Document 3] JP 2004-42345 A [Patent Document 4] Special Publication No. 2016-540901 Summary of the Invention [Problem to be solved by the invention]
[0008] In order for a laminated core to exhibit high performance under use conditions, it is required that a cured product (cured adhesive product) obtained from an adhesive composition for laminated electromagnetic steel sheets has excellent toughness, as shown in Patent Document 3. In particular, in recent years, the toughness of the cured adhesive product is required to have a high yield stress over a wide temperature range, including high temperatures (e.g., 120°C or higher). Specifically, for example, a yield stress of 60 MPa or more measured under conditions of 25°C and a yield stress of 20 MPa or more measured under conditions of 140°C are required. However, it has been extremely difficult to obtain a cured adhesive product having the above-mentioned excellent toughness from conventional adhesive compositions.
[0009] Next, when using electrical steel sheets to which the adhesive composition has been applied in the manufacture of laminated cores, the adhesive is required to be tack-free. In general, electromagnetic steel sheets to which an adhesive composition is applied are first coated with the adhesive composition on the surface of the electromagnetic steel sheet and dried, and then transported or stored in a state in which the electromagnetic steel sheets are stacked on top of each other (for example, in a state in which the electromagnetic steel sheets are rolled up in a roll). If the adhesive has tack in this state, the adhesive may adhere to other electromagnetic steel sheets during transportation or storage, and when the rolled electromagnetic steel sheet is unrolled to use the electromagnetic steel sheet, the adhesive may peel off from the electromagnetic steel sheet to which it should have been adhered. In addition, during the punching process, the adhesive composition on the electromagnetic steel sheet may stick to the punching device, etc. For this reason, when the magnetic steel sheets are simply being laminated (before they are finally bonded to form a laminated magnetic steel sheet), the adhesive composition applied to the magnetic steel sheets needs to have excellent tack-free properties.
[0010] Furthermore, an adhesive composition for laminating electromagnetic steel sheets is required to have the adhesive performance of the adhesive composition not deteriorated even when the electromagnetic steel sheet to which the adhesive composition is applied is stored for a long period of time (to have excellent adhesive performance even after long-term storage).
[0011] Under the above circumstances, the present inventors, referring to Patent Documents 1 and 2, evaluated a cured product obtained from a composition containing an epoxy resin such as a bisphenol A type and a general phenoxy resin. It was found that the glass transition temperature (heat resistance) of the cured product did not increase, and the tack-free property of the adhesive composition after application, the toughness of the cured adhesive at high temperatures, and the maintenance of adhesive performance after long-term storage were insufficient. Furthermore, it was found that simply changing the above phenoxy resin and epoxy resin and increasing the Tg (heat resistance) of the resulting cured adhesive product did not increase the yield stress (toughness) of the cured product as described above, nor did it improve the tack-free properties of the adhesive composition after application (Comparative Example 1). Next, when the above epoxy resin was changed to an epoxy resin having a softening temperature of 50°C to 150°C and / or an epoxy resin with three or more functionalities, the Tg (heat resistance) of the obtained cured adhesive increased and the yield stress at room temperature increased, but it was found that this alone was insufficient to maintain the toughness of the cured adhesive under high temperature conditions and the adhesive performance after long-term storage (Comparative Examples 3 and 5).
[0012] Therefore, an object of the present application is to provide an adhesive composition for laminating electromagnetic steel sheets, which has excellent tack-free properties before the laminated electromagnetic steel sheets are produced, has excellent adhesive performance even after long-term storage, and the obtained cured adhesive has excellent toughness over a wide temperature range. [Means for solving the problem]
[0013] As a result of intensive research into solving the above problems, the inventors have discovered that the desired effects can be obtained by an adhesive composition containing a tri- or higher functional epoxy resin (A), a phenoxy resin (B) having a glass transition temperature of more than 120°C in an uncured state, and an amine-based latent curing agent (C), wherein the epoxy resin (A) contains an epoxy resin having a softening temperature of 60°C or more, the phenoxy resin (B) is contained in a specific amount, and the glass transition temperature of the obtained cured adhesive product exceeds 160°C, thereby completing the present invention.
[0014] [1] An epoxy resin (AA) containing an epoxy resin (A) having three or more epoxy groups in one molecule; A phenoxy resin (B) having a glass transition temperature in an uncured state of greater than 120° C. as measured by differential scanning calorimetry; and Contains an amine-based latent hardener (C), The epoxy resin (A) contains an epoxy resin having a softening temperature of 60° C. or higher, the content of the phenoxy resin (B) is 20 to 80 parts by mass relative to 100 parts by mass of the epoxy resin (AA); The adhesive composition for laminating electrical steel sheets has a glass transition temperature of more than 160°C as measured by differential scanning calorimetry of the resulting cured adhesive. [2] The adhesive composition for laminating magnetic steel sheets according to [1], wherein the phenoxy resin (B) comprises at least one selected from the group consisting of phosphorus-containing phenoxy resins (B1), fluorene-containing phenoxy resins (B2), and bisphenol S skeleton-containing phenoxy resins (B3). [3] The adhesive composition for laminating electrical steel sheets according to [1] or [2], wherein the epoxy resin having a softening temperature of 60°C or higher comprises a phenol novolac type epoxy resin (A1) and / or a cresol novolac type epoxy resin (A2). [4] The adhesive composition for laminating electrical steel sheets according to any one of [1] to [3], wherein the content of the epoxy resin having a softening temperature of 60° C. or higher is 50 mass % or more based on the total amount of the epoxy resin (AA). [5] The adhesive composition for laminating electrical steel sheets according to any one of [1] to [4], wherein the epoxy resin (A) further comprises an epoxy resin having an N,N-diglycidylamino group, and the content of the epoxy resin having an N,N-diglycidylamino group is 50 mass % or less of the total amount of the epoxy resin (AA). [6] The adhesive composition for laminating electrical steel sheets according to [5], wherein the epoxy resin having an N,N-diglycidylamino group comprises an epoxy resin (A3) represented by formula (1) described below and / or an epoxy resin (A4) represented by formula (2) described below. [7] The adhesive composition for laminating electrical steel sheets according to any one of [1] to [6], wherein the content of the amine-based latent curing agent (C) is 5 to 70 parts by mass per 100 parts by mass of the epoxy resin (AA). [8] The adhesive composition for laminating electrical steel sheets according to any one of [1] to [7], further comprising a toughening agent (D). [9] The adhesive composition for laminating electrical steel sheets according to [8], wherein the toughening agent (D) has an average particle size of 0.005 to 0.6 μm and contains a core-shell type toughening agent (D1).
[10] The adhesive composition for laminating electrical steel sheets according to [8] or [9], wherein the content of the toughening agent (D) is 1 to 30 parts by mass per 100 parts by mass of the epoxy resin (AA).
[11] The adhesive composition for laminating electrical steel sheets according to any one of [1] to
[10] , wherein the content of the difunctional epoxy resin in the epoxy resin (AA) is 0 to 40 mass %.
[12] The adhesive composition for laminating electrical steel sheets according to any one of [1] to
[11] , wherein the adhesive cured product has a yield stress of 60 MPa or more measured at 25°C in accordance with JIS K7161, and a yield stress of 20 MPa or more measured at 140°C.
[0015]
[13] An iron core in which electromagnetic steel sheets and adhesive layers are alternately laminated, the adhesive layers being formed from the adhesive composition for laminating electromagnetic steel sheets according to any one of [1] to
[12] .
[14] The iron core according to
[13] , wherein the adhesive layer has a yield stress of 60 MPa or more measured at 25°C in accordance with JIS K7161, and a yield stress of 20 MPa or more measured at 140°C. Effect of the Invention
[0016] The adhesive composition for laminating electromagnetic steel sheets of the present invention has excellent tack-free properties from the time it is applied to the electromagnetic steel sheets until the production of the iron core (laminated iron core), and maintains excellent adhesive performance even when stored for long periods before the above-mentioned production, and the obtained cured adhesive product has excellent toughness over a wide temperature range. An iron core formed with the adhesive composition for laminating electrical steel sheets of the present invention has excellent adhesive performance and excellent toughness over a wide temperature range. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The following describes in detail an embodiment of the present invention. However, the description of the components described below is an example of an embodiment of the present invention, and the present invention is not limited to the following content unless the gist of the present invention is changed. In this specification, when the expression "~" is used, it is used as an expression including the numerical values before and after it. The method for producing each component described in this specification is not particularly limited unless otherwise specified, and may be, for example, a conventionally known method. In this specification, when at least one of the above tack-free property, adhesive performance, and toughness is superior in the adhesive composition for laminating electrical steel sheets of the present invention, it may be said that the "effects of the present invention are superior." The same applies when at least one of the adhesive performance and toughness is superior in the iron core formed with the adhesive composition for laminating electrical steel sheets of the present invention.
[0018] [Adhesive composition for laminating electromagnetic steel sheets] The adhesive composition for laminating electromagnetic steel sheets of the present invention (the composition of the present invention) is An epoxy resin (AA) containing an epoxy resin (A) having three or more epoxy groups in one molecule; A phenoxy resin (B) having a glass transition temperature (Tg) in an uncured state measured by differential scanning calorimetry (DSC) of more than 120°C, and Contains an amine-based latent hardener (C), The epoxy resin (A) contains an epoxy resin having a softening temperature of 60° C. or higher, the content of the phenoxy resin (B) is 20 to 80 parts by mass relative to 100 parts by mass of the epoxy resin (AA); The resulting adhesive composition for laminating electrical steel sheets has a cured product with a Tg of more than 160°C as measured by differential scanning calorimetry.
[0019] It has been found that the composition of the present invention contains not only an epoxy resin with a softening temperature of 60°C or higher, but also a phenoxy resin (B) with excellent cohesive strength, i.e., a Tg of more than 120°C, so that the resulting adhesive cured product can exhibit excellent yield stress not only at 25°C, but also over a wide temperature range including high temperatures. The above-mentioned points are considered to be the greatest features of the composition of the present invention. Each component contained in the composition of the present invention will be described in detail below.
[0020] <<Epoxy resin (AA)>> The composition of the present invention contains an epoxy resin (AA). The epoxy resin (AA) is a compound having a plurality of epoxy groups. The composition of the present invention contains the epoxy resin (AA), and thus can maintain high adhesive reliability to electrical steel sheets. In the present invention, the epoxy resin (AA) does not contain the phenoxy resin (B) described below, and does not contain the toughening agent (D) described below.
[0021] Epoxy equivalent of epoxy resin (AA) From the viewpoint of obtaining superior effects of the present invention, the epoxy equivalent of the epoxy resin (AA) is preferably 1000 g / eq or less, and more preferably 100 to 500 g / eq. In the present invention, the epoxy equivalent of the epoxy resin can be measured in accordance with JIS K 7236 standard using an automatic potentiometric titrator (HIRANUMA SANGYO CO., LTD., COM-1600ST) using chloroform as a solvent, adding a tetraethylammonium bromide acetate solution, and titrating with a 0.1 mol / L perchloric acid-acetic acid solution.
[0022] Molecular weight of epoxy resin (AA) The molecular weight of the epoxy resin (AA) is preferably 100 or more and less than 5,000, from the viewpoint of achieving superior effects of the present invention. The molecular weight of the epoxy resin (AA) can be calculated from the epoxy equivalent and the number of epoxy groups contained in the epoxy resin (AA).
[0023] <Epoxy resin (A)> The epoxy resin (AA) includes an epoxy resin (A) having three or more epoxy groups in one molecule. The number of epoxy groups that the epoxy resin (A) has in one molecule can be 20 or less, and from the viewpoint of obtaining superior effects of the present invention, 3 to 12 is preferable.
[0024] Epoxy resin (A) content From the viewpoint of obtaining superior effects of the present invention, the content of the epoxy resin (A) in the epoxy resin (AA) is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more. If the content is less than 50% by mass, the Tg of the cured product cannot be sufficiently increased, and problems remain in heat resistance.
[0025] <Epoxy resin with a softening temperature of 60°C or higher> In the composition of the present invention, the epoxy resin (A) contains an epoxy resin having a softening temperature of 60° C. or higher. The composition of the present invention contains the epoxy resin having a softening temperature of 60° C. or higher, and thus has excellent tack-free properties, adhesive performance, and toughness. The above-mentioned epoxy resins having a softening temperature of 60° C. or higher belong to the epoxy resin (A) and therefore have three or more epoxy groups in one molecule. The above-mentioned epoxy resins having a softening temperature of 60° C. or higher are sometimes called "solid epoxy resins."
[0026] ·Softening temperature In the present invention, the softening temperature of the solid epoxy resin is 60° C. or higher, and from the viewpoint of obtaining superior effects of the present invention, it is preferably 60 to 110° C. If it exceeds 110° C., the adhesive may have poor applicability to the steel plate and may have a reduced adhesive strength. In addition, from the viewpoint of obtaining superior effects of the present invention, the solid epoxy resin preferably contains an epoxy resin having a softening temperature of 60 to 80° C. and / or an epoxy resin having a softening temperature of more than 80° C. and not more than 110° C. In the present invention, the softening temperature of the epoxy resin can be determined in accordance with JIS K7206:2016.
[0027] From the viewpoint of achieving superior effects of the present invention, the solid epoxy resin preferably contains a phenol novolac type epoxy resin (A1) and / or a cresol novolac type epoxy resin (A2), and more preferably contains an epoxy resin (A1) and an epoxy resin (A2).
[0028] Phenol novolac type epoxy resin (A1) The phenol novolac type epoxy resin generally refers to a reaction product of a phenol novolac resin and epichlorohydrin. An example of the phenol novolac type epoxy resin (A1) is a compound represented by the following formula (6).
[0029] [ka] In formula (6), n is at least 1 and can be at most 18. The above n is preferably 1 to 10, from the viewpoint of achieving better effects of the present invention.
[0030] ·Cresol novolac epoxy resin (A2) The cresol novolac epoxy resin generally refers to a reaction product of a cresol novolac resin and epichlorohydrin. An example of the cresol novolac epoxy resin (A2) is the reaction product of a cresol novolac resin and epichlorohydrin represented by the following formula (7).
[0031] [ka] In formula (7), n is at least 1 and can be at most 18. The above n is preferably 1 to 10, from the viewpoint of achieving better effects of the present invention.
[0032] Solid epoxy resin content The content of the solid epoxy resin (when the solid epoxy resin contains the epoxy resin (A1) and the epoxy resin (A2), the total content of these) is preferably 50 mass % or more, more preferably 60 mass % or more, and even more preferably 70 mass % or more, of the total amount of the epoxy resin (AA), from the viewpoint of obtaining better effects of the present invention (particularly better tack-free properties and less adhesion between magnetic steel sheets). If it is less than 50 mass %, sufficient tack-free properties cannot be obtained, and the steel sheets may adhere to each other during storage.
[0033] Epoxy resins containing nitrogen atoms From the viewpoint of achieving superior effects of the present invention, the epoxy resin (A) preferably further contains an epoxy resin having a nitrogen atom (also referred to as a nitrogen-containing epoxy resin), and more preferably contains an epoxy resin having an N,N-diglycidylamino group (structure shown below). The nitrogen-containing epoxy resin does not include epoxy resins with a softening temperature of 60°C or higher. [ka] In the above structural formula, * represents a bond position. The epoxy resin having an N,N-diglycidylamino group (also referred to as a glycidylamino group-containing epoxy resin) preferably has 1 to 2 N,N-diglycidylamino groups in one molecule. The glycidylamino group-containing epoxy resin may further have an epoxy group other than the N,N-diglycidylamino group (for example, an epoxy group such as a glycidyl group or a glycidyloxy group). When the glycidylamino group-containing epoxy resin has one N,N-diglycidylamino group in one molecule, it may further have an epoxy group other than the N,N-diglycidylamino group. In the nitrogen-containing epoxy resin, a group having an epoxy group such as an N,N-diglycidylamino group can be bonded to a divalent or higher linking group. The linking group is not particularly limited. For example, a hydrocarbon group can be mentioned, and a hydrocarbon group having an aromatic hydrocarbon group is preferable.
[0034] Epoxy resin (A3), (A4) From the viewpoint of achieving superior effects of the present invention, the glycidylamino group-containing epoxy resin preferably contains an epoxy resin (A3) represented by the following formula (1) and / or an epoxy resin (A4) represented by the following formula (2), and more preferably contains at least an epoxy resin (A4). When the glycidylamino group-containing epoxy resin contains an epoxy resin (A4), it may further contain the epoxy resin (A3). [ka] (1) [ka] (2)
[0035] The nitrogen-containing epoxy resin is preferably in a liquid state at room temperature (25° C.). The nitrogen-containing epoxy resin belongs to the epoxy resin (A) and therefore has three or more epoxy groups in one molecule.
[0036] Content of epoxy resin containing nitrogen atoms The content of the nitrogen-containing epoxy resin (when the nitrogen-containing epoxy resin contains the epoxy resin (A3) and the epoxy resin (A4), the total content of these) is preferably 50 mass % or less, more preferably 10 to 40 mass %, and further preferably 20 to 30 mass %, of the total amount of the epoxy resin (AA).
[0037] From the viewpoint of obtaining superior effects of the present invention, the content of the epoxy resin (A4) is preferably 10 to 40% by mass of the total amount of the epoxy resin (AA). If it is less than 10% by mass, sufficient heat resistance may not be obtained, and if it exceeds 40% by mass, sufficient tack-free property may not be obtained. From the viewpoint of obtaining superior effects of the present invention, the content of the epoxy resin (A3) is preferably 0 to 20 mass % of the total amount of the epoxy resin (AA).
[0038] Epoxy resins other than epoxy resin (A) The epoxy resin (AA) may further contain an epoxy resin (other epoxy compound) other than the epoxy resin (A) having three or more epoxy groups in one molecule. Examples of the other epoxy compounds include monofunctional epoxy compounds having one epoxy group in one molecule, and difunctional epoxy resins (epoxy resins having two epoxy groups in one molecule). Examples of the bifunctional epoxy resin include bisphenol-type epoxy resins such as bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, brominated bisphenol A-type epoxy resins, hydrogenated bisphenol A-type epoxy resins, bisphenol S-type epoxy resins, and bisphenol AF-type epoxy resins; and epoxy resins having a bisphenyl group such as biphenyl-type epoxy resins. When the composition of the present invention further contains another epoxy compound, it preferably contains a difunctional epoxy resin, and more preferably contains a bisphenol A type epoxy resin.
[0039] Other epoxy compound content From the viewpoint of obtaining superior effects of the present invention (particularly tack-free property), the content of the other epoxy compounds is preferably 0 to 40 mass % in the epoxy resin (AA), and more preferably 0 to 10 mass %.
[0040] <<Phenoxy resin (B)>> The composition of the present invention contains a phenoxy resin (B) having a Tg of more than 120° C. in an uncured state as measured by differential scanning calorimetry (DSC). The composition of the present invention contains the phenoxy resin (B), and thus has excellent tack-free properties, adhesive performance, and toughness. Conventionally, resins obtained by increasing the molecular weight of low-molecular-weight epoxy compounds are called phenoxy resins, and the above-mentioned phenoxy resin (B) does not include the above-mentioned epoxy resin (AA).Furthermore, the above-mentioned phenoxy resin (B) does not include the toughening agent (D) described below.
[0041] Specific examples of phenoxy resin (B) Examples of the phenoxy resin (B) include phosphorus-containing phenoxy resin (B1), fluorene-containing phenoxy resin (B2), phenoxy resins having a bisphenol skeleton, phenoxy resins having a novolac skeleton, phenoxy resins having a naphthalene skeleton, and phenoxy resins having a biphenyl skeleton. Of these, from the viewpoint of achieving better effects of the present invention (particularly toughness), the phenoxy resin (B) preferably contains at least one selected from the group consisting of phosphorus-containing phenoxy resin (B1), fluorene-containing phenoxy resin (B2), and bisphenol S skeleton-containing phenoxy resin (B3). In addition to the above, from the viewpoint of achieving better heat resistance and adhesion to electromagnetic steel sheets, it is more preferable for the phenoxy resin (B3) to contain a bisphenol S skeleton-containing phenoxy resin.
[0042] <Phosphorus-containing phenoxy resin (B1)> The phosphorus-containing phenoxy resin (B1) is a phenoxy resin having phosphorus. From the viewpoint of achieving superior effects of the present invention, the phosphorus-containing phenoxy resin (B1) preferably has a skeleton represented by the following formula (B1-1). [ka] (B1-1) In formula (B1-1), R 1 each independently represents a hydrogen atom or a methyl group, m and n each independently is 1 or more, and m+n can be a value corresponding to the weight average molecular weight of the phenoxy resin (B) described later.
[0043] <Fluorene-containing phenoxy resin (B2)> The fluorene-containing phenoxy resin (B2) is a phenoxy resin having fluorene. From the viewpoint of achieving superior effects of the present invention, the fluorene-containing phenoxy resin (B2) preferably has a skeleton represented by the following formula (B2-1). [ka] (B2-1) In formula (B2-1), R 1 each independently represents a hydrogen atom or a methyl group, p and q each independently is 1 or more, and p+q can be a value corresponding to the weight average molecular weight of the phenoxy resin (B) described later.
[0044] <Bisphenol S skeleton-containing phenoxy resin (B3)> The bisphenol S skeleton-containing phenoxy resin (B3) is a phenoxy resin having a bisphenol S skeleton. From the viewpoint of achieving superior effects of the present invention, the phenoxy resin (B3) having a bisphenol S skeleton preferably has a skeleton represented by the following formula (B3-1). [ka] (B3-1) In formula (B3-1), R 1 each independently represents a hydrogen atom or a methyl group, r and s each independently is 1 or more, and r+s can be a value corresponding to the weight average molecular weight of the phenoxy resin (B) described later.
[0045] In addition, in formula (B1-1), formula (B2-1), and formula (B3-1), the terminal of each structural formula is not particularly limited. For example, an epoxy group or a hydrogen atom can be bonded to the above terminal. When an epoxy group is bonded to the above terminal, the above terminal and the epoxy group can be bonded via a linking group. The above linking group is not particularly limited.
[0046] <Glass transition temperature of phenoxy resin (B)> In the composition of the present invention, the glass transition temperature (Tg) of the phenoxy resin (B) in an uncured state exceeds 120°C as measured by differential scanning calorimetry (DSC). "Phenoxy resin (B) in an uncured state" refers to the phenoxy resin (B) in a state prior to being blended into the composition of the present invention. When the Tg of the phenoxy resin (B) contained in the composition of the present invention is within the above range, the adhesive cured product obtained from the composition of the present invention has excellent toughness and adhesive performance.
[0047] The glass transition temperature of the phenoxy resin (B) was measured using a differential scanning calorimeter DSC-50 manufactured by SHIMADZU CORPORATION, by heating the resin to 370°C at a heating rate of 15°C / min, and measuring the DSC curve in the temperature range of 50°C to 370°C. The temperature of the first inflection point of the DSC curve was determined as the glass transition temperature of the phenoxy resin (B).
[0048] When the phenoxy resin (B) has an epoxy group, the epoxy equivalent of the phenoxy resin (B) is preferably 5000 g / eq or more from the viewpoint of obtaining a better effect of the present invention. Even if the epoxy resin (A) / phenoxy resin (B) molecules are chemically bonded to each other and undergo phase separation in the cured resin, the interfacial strength is ensured and toughness is easily maintained. The phenoxy resin (B) may not have an epoxy group.
[0049] Weight average molecular weight of phenoxy resin (B) From the viewpoint of obtaining superior effects of the present invention, the weight average molecular weight of the phenoxy resin (B) is preferably 30,000 to 500,000, and more preferably 35,000 to 100,000. If it is less than 30,000, sufficient toughness cannot be obtained, and if it exceeds 100,000, the viscosity of the adhesive liquid increases, which may make it difficult to apply the adhesive liquid uniformly to the steel sheet. In the present invention, the weight average molecular weight (Mw) of the phenoxy resin can be a value calculated as a standard polystyrene equivalent measured by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent. The weight average molecular weight (Mw) of the phenoxy resin may be a catalog value.
[0050] <Phenoxy resin (B) content> In the composition of the present invention, the content of the phenoxy resin (B) is 20 to 80 parts by mass relative to 100 parts by mass of the total amount of the epoxy resin (AA). If the content of the phenoxy resin (B) is less than 20 parts by mass, the toughness of the obtained adhesive cured product may be insufficient. If the content of the phenoxy resin (B) exceeds 80 parts by mass, the Tg of the obtained adhesive cured product cannot exceed 160°C.
[0051] <Amine-based latent hardener (C)> The composition of the present invention contains an amine-based latent curing agent (C). There are several known methods for curing epoxy resins, but although acid anhydride and phenol-based curing agents improve adhesive strength, they have a slow curing speed and are therefore not suitable for the present invention. Also, ordinary polyamine curing agents cure too quickly and are therefore not suitable for the present invention. The composition of the present invention exhibits excellent effects of the present invention (particularly adhesive performance after long-term storage) by containing the amine-based latent curing agent (C). In the present invention, a latent curing agent means a curing agent whose reaction can be initiated by heating, etc. Unlike normal curing agents that react at room temperature (e.g., 25°C), a latent curing agent does not react at room temperature, or even if it does react, the reaction is very slight. The amine-based latent curing agent (C) has a nitrogen atom and can function as a curing agent for the epoxy resin (AA) and / or the phenoxy resin (B). In the present invention, since the phenoxy resin (B) does not have an epoxy group, or even if it has an epoxy group, the Mw of the phenoxy resin (B) is larger than that of the epoxy resin (AA), it is considered that most of the amine-based latent curing agent (C) reacts with the epoxy resin (AA).
[0052] Specific examples of amine-based latent hardeners (C) Examples of the amine-based latent curing agent (C) include dicyandiamide, modified polyamines, hydrazides, 4,4'-diaminodiphenylsulfone (DDS), ureas such as DCMU: 3-(3,4-dichlorophenyl)-1,1-dimethylurea, imidazole compounds such as 2-ethyl-4-methylimidazole, and melamine. These may be used alone or in combination of two or more. From the viewpoint of obtaining a more excellent effect of the present invention, the amine-based latent curing agent (C) preferably contains at least one selected from the group consisting of dicyandiamide, ureas, 4,4'-diaminodiphenyl sulfone, and imidazole-based compounds, More preferably, the combination includes dicyandiamide and a urea and / or an imidazole-based compound, or includes 4,4'-diaminodiphenyl sulfone (4,4'-diaminodiphenyl sulfone may be used alone); A combination of dicyandiamide and 3-(3,4-dichlorophenyl)-1,1-dimethylurea, or 4,4'-diaminodiphenyl sulfone is more preferred.
[0053] Amine-based latent hardener (C) content The content of the amine-based latent curing agent (C) (when the amine-based latent curing agent (C) contains a plurality of types of amine-based latent curing agents (C), the total content of the plurality of types of amine-based latent curing agents (C)) is preferably 5 to 70 parts by mass relative to 100 parts by mass of the epoxy resin (AA) from the viewpoint of achieving superior effects of the present invention. When the amine-based latent curing agent (C) contains dicyandiamide and a urea, the total content of the amine-based latent curing agent (C) is preferably 5 to 20 parts by mass based on 100 parts by mass of the epoxy resin (AA). When the amine-based latent curing agent (C) contains 4,4'-diaminodiphenyl sulfone, the content of the amine-based latent curing agent (C) is preferably 25 to 50 parts by mass based on 100 parts by mass of the epoxy resin (AA).
[0054] · Toughener (D) From the viewpoint of achieving even greater toughness in the obtained cured adhesive product, it is preferred that the composition of the present invention further contains a toughening agent (D). The toughening agent (D) refers to a compound that can impart additional toughness to the resulting cured adhesive. The toughening agent (D) is preferably composed of a flexible polymer. Examples of the toughening agent (D) include core-shell type, rubber-modified epoxy resins, and urethane-modified epoxy resins. The toughening agent (D) is not included in the epoxy resin (AA), the phenoxy resin (B), or the amine-based latent curing agent (C). The toughening agent (D) may or may not react with the amine-based latent curing agent (C), the epoxy resin (AA) or the phenoxy resin (B).
[0055] From the viewpoint of achieving superior effects of the present invention (particularly toughness), the toughening agent (D) preferably contains at least one selected from the group consisting of a core-shell type, a rubber-modified epoxy resin, and a urethane-modified epoxy resin, more preferably contains a core-shell type toughening agent, and further preferably contains a core-shell type toughening agent (D1) having an average particle size of 0.05 to 0.2 μm.
[0056] Core-shell type toughening agent One preferred embodiment of the core-shell type toughening agent is in particulate form. The core-shell type toughening agent has a core layer and a shell layer. Examples of the core-shell type toughening agent include rubber particles having a two-layer structure in which the outer shell layer is made of a glassy polymer and the inner core layer is made of a rubbery polymer, and rubber particles having a three-layer structure in which the outer shell layer is made of a glassy polymer, the middle layer is made of a rubbery polymer, and the core layer is made of a glassy polymer. The glassy polymer is made of, for example, a polymer of methyl (meth)acrylate and / or a polymer of styrene. The rubbery polymer layer is made of, for example, a butyl acrylate polymer (butyl rubber), silicone rubber, or polybutadiene.
[0057] Average particle size of toughening agent (D) The average particle size of the toughening agent (D) is preferably 0.005 μm or more and 0.6 μm or less, more preferably 0.05 μm or more and 0.2 μm or less, from the viewpoint of obtaining a cured adhesive having superior toughness and from the viewpoint of not lowering Tg. If the particle size is less than 0.005 μm, the particles are poorly dispersed in the epoxy resin, and if it exceeds 0.6 μm, the heat resistance may be deteriorated.
[0058] The average particle diameter of the toughening agent (D) refers to the particle diameter at 50% cumulative (50% volume cumulative diameter) obtained by measuring the volume-based particle size distribution using a laser diffraction particle size distribution measuring device. As a laser diffraction particle size distribution measuring device, for example, the "Microtrac MT3000II series" laser diffraction scattering particle size distribution measuring device manufactured by Microtrac Bell can be mentioned. The matters concerning the core-shell type toughening agent and the average particle size of the toughening agent (D) described above are the same as those concerning the core-shell type toughening agent (D1).
[0059] Rubber-modified epoxy resin A rubber-modified epoxy resin is an epoxy resin that has two or more epoxy groups and has a rubber skeleton. Examples of rubber forming the skeleton include polybutadiene and acrylonitrile butadiene rubber (NBR). The epoxy equivalent of the rubber-modified epoxy resin is preferably 200 g / eq or more and 500 g / eq or less, from the viewpoint of obtaining superior effects of the present invention.
[0060] ·Urethane modified epoxy resin The urethane-modified epoxy resin is an epoxy resin having two or more epoxy groups and a polyurethane skeleton. The polyurethane forming the above skeleton is not particularly limited as long as it is a polymer having a plurality of urethane bonds and / or urea bonds. The epoxy equivalent of the urethane-modified epoxy resin is preferably 200 g / eq or more and 500 g / eq or less, from the viewpoint of obtaining superior effects of the present invention.
[0061] -Toughener (D) content When the composition of the present invention further contains a toughening agent (D), the content of the toughening agent (D) (when there are two or more types of toughening agents (D), the total content of the two or more types of toughening agents (D)) is preferably 1 to 30 parts by mass, and more preferably 5 to 20 parts by mass, per 100 parts by mass of the epoxy resin (AA). When it is less than 1 part by mass or more than 30 parts by mass, the toughening effect is hardly exhibited and the heat resistance is deteriorated.
[0062] (Additives) The composition of the present invention may further contain various additives as necessary within the range in which the effects of the present invention are exhibited. Examples of the additives include fillers, reaction retarders, antioxidants, antioxidants, pigments, dyes, plasticizers, silane coupling agents, thixotropy-imparting agents, adhesion-imparting agents, flame retardants, antistatic agents, ultraviolet absorbers, surfactants, dispersants, dehydrating agents, and solvents.
[0063] ·solvent Examples of the solvent include ketone-based solvents such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; ester-based solvents such as ethyl acetate and butyl acetate; aliphatic solvents such as n-hexane; alicyclic solvents such as cyclohexane; and aromatic solvents such as toluene, xylene, and cellosolve acetate. The amount of the solvent is preferably 80 to 300 parts by mass relative to 100 parts by mass of the epoxy resin (AA). If the amount is less than 80 parts by mass, the viscosity increases and uniform application becomes difficult, whereas if the amount is more than 300 parts by mass, it becomes difficult to apply the adhesive layer to the steel sheet surface with a precise thickness.
[0064] The method for producing the composition of the present invention is not particularly limited, and the composition can be obtained, for example, by mixing the above-mentioned epoxy resin (A), phenoxy resin (B), amine-based latent curing agent (C), other epoxy compounds that can be used as necessary, toughening agent (D), and various additives, using a stirrer such as a mixing mixer.
[0065] The composition of the present invention can be used as an adhesive composition for laminating electrical steel sheets.
[0066] The composition of the present invention can be cured, for example, under conditions of 140 to 250° C. The curing temperature is preferably equal to or higher than the temperature at which the amine-based latent curing agent (C) is activated. Pressure may be applied during the curing. After curing, the composition of the present invention becomes the above-mentioned "cured adhesive obtained from the composition of the present invention" or an adhesive layer of an iron core formed from the composition of the present invention, which will be described later.
[0067] <Glass transition temperature of cured adhesive> In the present invention, the cured adhesive (or adhesive layer; the same applies hereinafter) obtained from the composition of the present invention has a glass transition temperature of more than 160°C as measured by differential scanning calorimetry. Since the glass transition temperature of the cured adhesive exceeds 160° C., the composition of the present invention has excellent toughness even at high temperatures. The glass transition temperature of the cured adhesive is preferably 180° C. or higher, and more preferably 200 to 280° C., from the viewpoint of achieving superior effects of the present invention.
[0068] ·Method for measuring the glass transition temperature of cured adhesive The glass transition temperature of the cured adhesive was measured using a SHIMADZU DSC-50 differential scanning calorimeter by raising the temperature to 370°C at a heating rate of 15°C / min and measuring the DSC curve in the temperature range of 50°C to 370°C. In the present invention, the temperature of the first inflection point in the above DSC curve was basically determined to be the glass transition temperature of the cured adhesive (adhesive layer). Furthermore, when the cured adhesive has a phase structure such as a sea-island structure or a co-continuous phase structure, and the DSC curve indicates the glass transition temperatures of multiple resins that form the above-mentioned phase structure, the glass transition temperature of the resin contained in the greater amount in the cured adhesive, or the glass transition temperature of the matrix resin (not the domain), was taken as the glass transition temperature of the cured adhesive (adhesive layer). In the present invention, since the content of the epoxy resin (AA) is greater than the content of the phenoxy resin (B), the content of the cured product of the epoxy resin (AA) and the amine-based latent curing agent (C) may be greater than the content of the phenoxy resin (B) in the obtained cured adhesive.
[0069] <Yield stress at 25℃ ≧ 60MPa> The adhesive cured product obtained by curing the composition of the present invention preferably has a yield stress of 60 MPa or more, and more preferably 80 to 200 MPa, measured under conditions at 25°C, from the viewpoint of achieving greater effects of the present invention (particularly toughness) and making the iron core less susceptible to fracture or deformation even when rotated at high speed.
[0070] <Yield stress at 140℃ ≧ 20MPa> The adhesive cured product obtained by curing the composition of the present invention preferably has a yield stress of 20 MPa or more, and more preferably 35 MPa or more, measured at 140°C, from the viewpoint of providing better effects of the present invention (particularly toughness) and making the iron core less susceptible to fracture or deformation even when rotated at high speed under high temperature conditions.
[0071] Conventionally, it is said that the temperature of a rotor with embedded permanent magnets during continuous rotation rises to about 140°C if there is no cooling with engine oil or the like (Reference: Satoru Hirano, "Heat flow characteristics in a rotating double cylinder simulating the motor structure for electric vehicles", page 9, 2013, Graduate School of Tsukuba University Thesis 12102-6725). Therefore, if the yield stress of the adhesive cured product measured under conditions of 140°C is 20 MPa or more, it is considered that the strength (toughness) of the adhesive cured product can be sufficiently maintained under high temperature conditions even without cooling with engine oil, and when the composition of the present invention is applied to a laminated iron core, it is considered that the deformation and destruction of the laminated iron core during high speed rotation can be suppressed.
[0072] The above-mentioned adhesive cured product preferably has a yield stress of 60 MPa or more measured at 25°C and a yield stress of 20 MPa or more measured at 140°C in accordance with JIS K7161, and more preferably has a yield stress of 85 MPa or more measured at 25°C and a yield stress of 35 MPa or more measured at 140°C.
[0073] In the present invention, the yield stress (tensile yield stress) at 25°C of the cured adhesive obtained by curing the composition of the present invention is measured under conditions at 25°C in accordance with JIS K 7161:2014. The yield stress of the cured adhesive measured at 140°C is measured under conditions at 140°C in accordance with JIS K 7161:2014.
[0074] [Iron core] An iron core formed from the composition of the present invention comprises magnetic steel sheets and adhesive layers laminated alternately, the adhesive layers being formed from the adhesive composition for laminating magnetic steel sheets of the present invention.
[0075] The iron core suitable for the present invention has an adhesive layer formed from the composition of the present invention, and therefore has excellent adhesive performance and excellent toughness over a wide temperature range, and is therefore considered to be less susceptible to fracture or deformation even when rotated at high speeds under a wide range of temperature conditions, including high temperatures.
[0076] The adhesive composition for laminating electromagnetic steel sheets used in this iron core is not particularly limited, so long as it is the adhesive composition for laminating electromagnetic steel sheets of the present invention (in the case of an iron core formed with the composition of the present invention, it will be simply referred to as the "composition"). Furthermore, there are no particular limitations on the type of electrical steel sheet used in the iron core formed from the composition of the present invention, and examples include conventionally known electrical steel sheets.
[0077] The adhesive layer preferably has a yield stress of 60 MPa or more when measured at 25° C. in accordance with JIS K7161, and a yield stress of 20 MPa or more when measured at 140° C. The above-mentioned yield stress of the adhesive layer in the iron core formed from the composition of the present invention is similar to the yield stress of the cured adhesive obtained by curing the above-mentioned composition of the present invention.
[0078] (Adhesion to electromagnetic steel sheets) The adhesive strength of the adhesive of the present invention to electromagnetic steel sheets is preferably such that the shear strength according to JIS K 6850 at 25°C and / or 140°C is 7.0 MPa or more.
[0079] (Manufacturing method) There are no particular limitations on the method for producing an iron core formed from the composition of the present invention, so long as the composition of the present invention is used. Examples of the production method include a coating step of coating the composition onto an electrical steel sheet; A punching process for punching out the electromagnetic steel sheet obtained in the coating process; A lamination process of laminating the punched electromagnetic steel sheets after the punching process; and The method includes a curing step of heating the laminate obtained in the lamination step to integrate the laminate.
[0080] ·Coating process The coating step is a step of coating the composition of the present invention onto an electrical steel sheet. The method for applying the composition to the electrical steel sheet is not particularly limited, and examples thereof include a roll coater method, a gravure coater method, an air doctor coater method, a blade coater method, a knife coater method, a rod coater method, a kiss coater method, a bead coater method, a cast coater method, a rotary screen method, a slot orifice coater method, a spray coating method, an inkjet method, a spin coating method, and an electrodeposition coating method.
[0081] In the coating step, the composition may be coated on at least one surface of the electrical steel sheet.
[0082] Thickness of composition after application After the coating step, the thickness of the composition after coating and drying is preferably 1 to 20 μm, particularly preferably 2 to 10 μm, taking into consideration the unevenness of the magnetic steel sheet and ease of pressure bonding of the magnetic steel sheet.
[0083] ·Drying process When the composition used in the iron core formed from the composition of the present invention contains a solvent, it is preferable to provide a drying step for removing the solvent from the composition after coating. After the drying step (or after the coating step if there is no drying step), a composite material in which the composition of the present invention is applied to an electromagnetic steel sheet can be obtained. Examples of the drying method in the drying step include hot air drying, induction heating, and vacuum heating. It is preferable to continue drying until the composition on the magnetic steel sheet becomes non-sticky (so-called tack-free).
[0084] The temperature in the drying process is not particularly limited, but if the reaction of the epoxy resin proceeds too far, the adhesion during curing will be insufficient, while if the reaction does not proceed at all, tack will occur depending on the composition of the epoxy resin, causing problems such as blocking between the steel sheets. In order to increase the productivity of the coating and drying processes, it is preferable to dry at a relatively high temperature for a short period of time. Specifically, it is preferable to dry at 150°C or higher for several to several tens of seconds.
[0085] The composite material obtained as described above may be stored, for example, in a rolled or coiled state, or in a stacked state. The adhesive layer of the composite material has excellent tack-free properties, so that the adhesive layer will not peel off from the composite material when the stacked composite materials are spread out for use.
[0086] Punching process The punching step is a step of punching the composite material. Examples of a method for punching the composite material include shear processing. The shape of the punched composite material is not particularly limited.
[0087] ·Lamination process The lamination step is a step of laminating the composite materials punched in the punching step. The number of sheets of the composite material used for lamination is not particularly limited. The composite material may be laminated so that the magnetic steel sheets and the composition are laminated alternately.
[0088] ·Curing process The curing step is a step of heating the laminate obtained in the lamination step to integrate the laminate. The heating temperature in the curing step is preferably 130 to 300°C. When pressure is applied in the curing step, the pressure is preferably 0.1 to 10 MPa. In the curing step, the method of applying heat and pressure is not particularly limited. After the curing step, an iron core formed from the composition of the present invention can be obtained. EXAMPLES
[0089] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0090] [Electromagnetic steel sheet] Non-oriented electrical steel sheets with a thickness of 0.15 mm and a yield strength of 200 to 550 MPa were used.
[0091] [Adhesive composition for laminating electromagnetic steel sheets] Each composition was produced by mixing the components in the composition (parts by mass) shown in Table 1 below at 25°C. The amounts of phenoxy resin (B) and YP-50 shown in Table 1 are the net amounts of phenoxy resin, and the amount of toughening agent (D) is the net amount of toughening agent.
[0092] Details of each component shown in Table 1 are as follows. (Epoxy resin with three or more functional groups (A)) (Solid epoxy resin) Phenol novolac epoxy resin: Phenol novolac epoxy resin with 7 epoxy groups per molecule. Epoxy equivalent: 190g / eq. Product name: EPPN201, manufactured by Nippon Kayaku Co., Ltd. Softening temperature: 65-78°C. Solid at room temperature (25°C). · Cresol novolac epoxy resin: Cresol novolac epoxy resin with 3 to 10 epoxy groups per molecule. Epoxy equivalent: 209 g / eq. Product name: YDCN-704A, manufactured by Nippon Steel Chemical & Material Co., Ltd. Softening temperature: 87 to 93°C. Solid at room temperature (25°C).
[0093] (Nitrogen-containing epoxy resin) Nitrogen-containing epoxy resin (1): Trifunctional epoxy resin represented by the following formula (1). Epoxy equivalent: 97 g / eq. Product name: EP-3950E, manufactured by ADEKA Corporation. Liquid at room temperature (25°C). [ka] (1) Nitrogen-containing epoxy resin (2): 4-functional epoxy resin represented by the following formula (2). Epoxy equivalent: 110 g / eq. Product name: YH404, manufactured by Nippon Steel Chemical & Material Co., Ltd. Liquid at room temperature (25°C). [ka] (2)
[0094] (Epoxy resins other than epoxy resin (A)) Bisphenol A epoxy resin: Bisphenol A epoxy resin. Bifunctional. Molecular weight 380, epoxy equivalent 190±5g / eq, Epicoat 828, manufactured by Mitsubishi Chemical Corporation. Liquid at room temperature (25°C).
[0095] (Phenoxy resin (B) with Tg exceeding 120℃) YPS-007: Phenoxy resin with a bisphenol S structure. Manufactured by Nippon Steel Chemical & Material Co., Ltd. Tg in uncured state exceeds 120°C. Mw 40,000 to 100,000.
[0096] ERF-001: Phosphorus-containing phenoxy resin. Manufactured by Nippon Steel Chemical & Material Co., Ltd. Tg exceeds 120°C in the uncured state. Mw 40,000 to 100,000.
[0097] ·F-Resin: A fluorene-containing phenoxy resin prepared as follows. Tg in the uncured state is over 120°C. Mw is 40,000 or more and 100,000 or less. ··Preparation of F-Resin In a mixed solvent of cyclohexanone and toluene, 1.02 moles of bisphenol A glycidyl ether and 1.0 moles of 9,9-bis(4-hydroxyphenyl)fluorene (structure below) were reacted for 8 hours at a temperature of 150°C to 170°C in the presence of a catalytic amount of 2-ethyl-4-methylimidazole (2E4MZ, manufactured by Shikoku Chemical Industry Co., Ltd.), to obtain a solution containing fluorene-containing phenoxy resin as a solid content of 40 mass%.
[0098] [ka]
[0099] The obtained fluorene-containing phenoxy resin is called "F-Resin". The structure of F-Resin is represented by the following formula (B2-2). [ka] (B2-2) In formula (B2-2), R 1 each represents a methyl group, p and q are each independently 1 or more, and p+q is a value corresponding to the above weight average molecular weight.
[0100] (Comparison) YP-50: Bisphenol A phenoxy resin with Tg 84℃. Product name: YP-50, manufactured by Nippon Steel Chemical & Material Co., Ltd., Tg 84℃, Mw 60,000~70,000 (catalog value).
[0101] (Toughening Agent (D)) Kane Ace MX-154 (core-shell type toughening agent (D1)): A mixture containing 33% by mass of core-shell type rubber particles. The core-shell type rubber particles function as a toughening agent. Product name: Kane Ace MX-154, manufactured by Kaneka Corporation. The value shown in the Kane Ace MX-154 column is the net amount of core-shell type rubber particles in Kane Ace MX-154. Average particle size: 0.1 μm. EPR-21 (rubber modified epoxy): Rubber modified epoxy resin. Product name: EPR-21, manufactured by ADEKA. Epoxy equivalent: 200g / eq.
[0102] (Amine-based latent hardener (C)) Dicyandiamide: ADEKA EH-3636AS DCMU: 3-(3,4-dichlorophenyl)-1,1-dimethylurea, manufactured by Hodogaya UPL Co., Ltd. DDS: 4,4′-diaminodiphenyl sulfone, manufactured by Wakayama Seika Kogyo Co., Ltd.
[0103] (solvent) Cyclohexanone
[0104] (Evaluation of cured adhesive) Glass transition temperature (Tg) measurement Each composition produced as described above was cast onto a release film to a thickness of 200 μm and cured in an oven at 150° C. for 1 hour. Differential scanning calorimetry (DMC measurement, heating rate 10° C. / min) was performed using the resulting cured adhesive to measure the glass transition temperature of the cured adhesive. The results are shown in Table 1 in the column "Glass transition temperature of cured adhesive." Evaluation criteria In the present invention, the Tg of the cured adhesive exceeds 160°C.
[0105] (Evaluation of cured adhesive: toughness) Tensile test pieces for each of the compositions produced as described above were prepared in accordance with JIS K 7161 (2014) by the following method.
[0106] ·Preparation of tensile test specimens Tensile test pieces were prepared according to JIS K 7161 (2014) using each composition prepared as described above. First, each composition prepared as described above was cast onto a release film to a thickness of 100 μm, and then vacuum degassed for 3 days. Next, the obtained film was cured in a 150° C. oven for 1 hour. The obtained adhesive cured product was punched into a No. 1 dumbbell shape to prepare a tensile test piece.
[0107] Tensile Test Using each of the tensile test pieces prepared as described above, the yield stress of the adhesive cured product (adhesive layer) obtained from the composition of the present invention was measured under conditions of 25°C or 140°C and 50% RH ± 5% RH using a thermostatic universal material testing machine Model 5966 (manufactured by Instron Co., Ltd.) in accordance with JIS K 7161: 2014. The yield strength of five tensile test pieces was measured at a tensile speed of 5 mm / min, a gauge length of 20 mm (using a contact extensometer), and a chuck length of 40 mm, and the average value was calculated. The yield strength (average value) under the condition of 25°C is shown in the "Toughness at room temperature (stress / MPa@25°C)" column of Table 1. The yield strength (average value) under the condition of 140°C is shown in the "Toughness at high temperature (stress / MPa@140°C)" column of Table 1.
[0108] Resilience assessment criteria If the yield stress at 25°C (assessment of toughness at room temperature) was 60 MPa or more and the yield stress at 140°C (assessment of toughness under high temperature conditions) was 20 MPa or more, it was evaluated as having excellent toughness not only under room temperature conditions but also under high temperature conditions. When the yield stress at 25° C. was less than 60 MPa, or when the yield stress at 140° C. was less than 20 MPa, the toughness was evaluated as poor.
[0109] (Tack-free property of the composition after drying) - Method for evaluating tack-free properties Each of the compositions produced as described above was cast onto an electromagnetic steel sheet to a thickness of 20 μm, and then held in an oven at 130° C. for 30 minutes to dry the solvent in each composition. The results are shown in Table 1 under the column "Tack-free property after drying." · Evaluation criteria for tack-free properties If the composition after drying was touched with a finger and felt no stickiness, it was evaluated as having excellent tack-free properties and was indicated by "◯". If the dried composition felt sticky when touched with a finger, but did not peel off from the magnetic steel sheet when a finger was pressed against the dried composition and then released, the tack-free property was evaluated as being somewhat excellent, and this was indicated by "Δ". If the dried composition felt sticky when touched with a finger, and if the dried composition peeled off from the electromagnetic steel sheet when a finger was pressed against the dried composition and then released, the tack-free property was evaluated as being poor, and this was indicated by "X".
[0110] (Evaluation of cured adhesive: shear strength) Shear strength (initial) Two electromagnetic steel sheets were prepared, and each composition produced as described above was cast onto the first electromagnetic steel sheet to a thickness of 6 μm, and then the sheet was kept in an oven at 130° C. for 10 minutes to dry the solvent in each composition. Another magnetic steel sheet was laminated to the dried composition on the magnetic steel sheet to form a laminate, and the laminate was cured in an oven at 160° C. for 1 hour to obtain a test piece. Using the above test pieces, the initial shear strength was measured under the condition of 140° C. in accordance with JIS K 6850. The results are shown in the column of “Shear strength (initial) / MPa@140° C.” in Table 1.
[0111] -Shear strength (40℃ for 6 months) Two electromagnetic steel sheets were prepared, and each composition produced as described above was cast onto the first electromagnetic steel sheet to a thickness of 6 μm. The first electromagnetic steel sheet was then held in an oven at 130° C. for 10 minutes to dry out the solvent in each composition, and the electromagnetic steel sheet having the dried composition was then stored in an oven at 40° C. for six months. After 6 months of storage, another electromagnetic steel sheet was attached to the composition on the electromagnetic steel sheet to form a laminate, and the laminate was cured in an oven at 150° C. for 1 hour to obtain a test specimen. Using the above test pieces, the shear strength was measured under the condition of 140° C. in accordance with JIS K 6850. The results are shown in the column of “Shear strength (40° C. for 6 months) / MPa@140° C.” in Table 1.
[0112] Evaluation criteria for deterioration of adhesive strength after long-term storage When both the initial shear strength and the shear strength after 6 months of storage were 7.0 MPa or more, it was evaluated that the decrease in adhesive strength after long-term storage was suppressed. When the initial shear strength was 7.0 MPa or more but the shear strength after 6 months of storage was less than 7.0 MPa, it was evaluated that the decrease in adhesive strength after long-term storage could not be suppressed. When the initial shear strength was less than 7.0 MPa, it was evaluated that the adhesive strength under high temperature conditions was low to begin with.
[0113] [Table 1]
[0114] As shown in the results in Table 1, Comparative Example 1, in which the content of the phenoxy resin (B) was less than the specified range, had poor toughness and poor tack-free properties under room temperature conditions. In Comparative Example 2, in which the content of phenoxy resin (B) was higher than the specified range, the resulting cured adhesive had a low glass transition temperature, poor toughness under high temperature conditions, and low adhesive strength both before and after long-term storage. In Comparative Examples 3 and 5, which did not contain the phenoxy resin (B) but instead contained a phenoxy resin with a glass transition temperature of 120°C or less in an uncured state, the glass transition temperature of the resulting cured adhesive was not low, but the toughness under high temperature conditions was significantly reduced and the adhesive strength under high temperature conditions was low both before and after long-term storage. In Comparative Example 4, which did not contain the specified epoxy resin (A) but contained a bifunctional epoxy resin instead, the glass transition temperature of the obtained cured adhesive was low, the toughness was poor both at room temperature and at high temperatures, and the tack-free properties were poor, and the adhesive strength was low both before and after long-term storage.
[0115] On the other hand, the composition of the present invention has excellent tack-free properties before the laminated electrical steel sheet is produced, has excellent adhesive performance even after long-term storage, and the obtained cured adhesive has excellent toughness over a wide temperature range.
[0116] From the above results, it is believed that the iron core formed from the composition of the present invention has an adhesive layer formed from the composition of the present invention, and the adhesive layer has excellent adhesive performance and toughness over a wide temperature range, so that the iron core formed from the composition of the present invention is less likely to break or deform even when rotated at high speeds under a wide range of temperature conditions, including high temperatures.
[0117] This application claims priority to Japanese Patent Application No. 2021-102360, filed on June 21, 2021, the disclosure of which is incorporated herein in its entirety.
Claims
1. an epoxy resin (AA) containing an epoxy resin (A) having three or more epoxy groups in one molecule; A phenoxy resin (B) having a glass transition temperature in an uncured state of more than 120° C. as measured by differential scanning calorimetry; and Contains an amine-based latent curing agent (C), The epoxy resin (A) contains an epoxy resin having a softening temperature of 60° C. or higher, the content of the epoxy resin having a softening temperature of 60° C. or more is 50 mass% or more based on the total amount of the epoxy resin (AA), the content of the phenoxy resin (B) is 20 to 80 parts by mass relative to 100 parts by mass of the epoxy resin (AA); The adhesive composition for laminating electrical steel sheets has a glass transition temperature of more than 160°C as measured by differential scanning calorimetry of the resulting cured adhesive.
2. 2. The adhesive composition for laminating magnetic steel sheets according to claim 1, wherein the phenoxy resin (B) comprises at least one selected from the group consisting of a phosphorus-containing phenoxy resin (B1), a fluorene-containing phenoxy resin (B2), and a bisphenol S skeleton-containing phenoxy resin (B3).
3. 3. The adhesive composition for laminating electrical steel sheets according to claim 1 or 2, wherein the epoxy resin having a softening temperature of 60° C. or higher comprises a phenol novolac type epoxy resin (A1) and / or a cresol novolac type epoxy resin (A2).
4. 3. The adhesive composition for laminating electrical steel sheets according to claim 1, wherein the epoxy resin (A) further comprises an epoxy resin having an N,N-diglycidylamino group, and the content of the epoxy resin having an N,N-diglycidylamino group is 50 mass% or less of the total amount of the epoxy resin (AA).
5. The adhesive composition for laminating electrical steel sheets according to claim 4, wherein the epoxy resin having an N,N-diglycidylamino group comprises an epoxy resin (A3) represented by the following formula (1) and / or an epoxy resin (A4) represented by the following formula (2): 【Chemistry 1】 (1) 【Chemistry 2】 (2)
6. 3. The adhesive composition for laminating electrical steel sheets according to claim 1, wherein the content of the amine-based latent curing agent (C) is 5 to 70 parts by mass per 100 parts by mass of the epoxy resin (AA).
7. The adhesive composition for laminating electrical steel sheets according to claim 1 or 2, further comprising a toughening agent (D).
8. The adhesive composition for laminating electrical steel sheets according to claim 7, wherein the toughening agent (D) has an average particle size of 0.005 to 0.6 μm and includes a core-shell type toughening agent (D1).
9. The adhesive composition for laminating electrical steel sheets according to claim 7, wherein the content of the toughening agent (D) is 1 to 30 parts by mass per 100 parts by mass of the epoxy resin (AA).
10. 3. The adhesive composition for laminating electrical steel sheets according to claim 1, wherein the content of the difunctional epoxy resin in the epoxy resin (AA) is 0 to 40 mass%.
11. 3. The adhesive composition for laminating electrical steel sheets according to claim 1 or 2, wherein the adhesive cured product has a yield stress of 60 MPa or more when measured at 25°C in accordance with JIS K7161, and a yield stress of 20 MPa or more when measured at 140°C.
Citation Information
Patent Citations
JP1973100602A
Laminated silicon steel sheet having excellent workability
JP2002146492A
Motor for electric vehicle or laminated plate for generator and motor or generator
JP2004042345A
Anisotropic conductive adhesive composition
JP2009517498A
Method of manufacturing laminated core
JP2014096429A